Social Life And Islamic Education On Ethnic Madurese And Malays In The Sungai Besar Besar Darat - Abdullah Abdullah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
This research was highly intention by the researcher's interest in social life and Islamic education on ethnic Madurese and Malays in the Sungai Besar, Darat Besar. Although there have been ethnic conflicts in several areas in West Kalimantan, but it contrast to the two ethnic groups namely Malay and Madurese in the area in Sungai Pinyuh Subdistrict and Sungai Besar, Darat Besar. Both ethnic relations are fairly good (harmonious). The focus of this research was to describe how Islamic Education has big influence in people social life. The method in this research was descriptive with qualitative research form and historical approach. The subjects of this research are religious leaders, local political figures, government officials, Karang Taruna community, BPD and Madurese and Malay Communities. The data in this research study was interviews and documentation. Data collection techniques conducted in this research used data reduction, data presentation and drawing the conclusion. The result of this study is the education and social condition of the community seems very good, with harmony atmosphere in society. In Sungai Bakau Besar Darat, even though they are have different ethnicities and religions, but they can live in harmony, as the way to live together peacefully. They respect each other and make their differences as a new lesson for seeking the pleasure of Allah SWT.